2019
DOI: 10.1039/c9ra08772a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-level understanding of interface interactions in a halloysite nanotubes–PLA nanocomposite

Abstract: To understand the nature of the bonding mechanism between poly(lactic acid) (PLA) and halloysite nanotubes (HNT), a first-principles DFT study was performed on the adsorption behavior of the PLA monomer, lactic acid (LA), on the outer, inner, and edge surfaces of the HNT. The role of LA functional groups, and its orientation behavior in the formation of bonds with HNT are systematically studied.Analysis of the adsorption energy, total and partial electron density of states (DOS), electric charge transfer betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Comparison of the band shapes calculated in the two considered approaches (Figure 3) allows one to note that, in the cluster approach, the valence band width is larger; however, the forbidden gap is reproduced well. In addition, the analysis of the results of this study makes it possible to associate the band of free states (position b) with the 3s states of aluminum, which correlates with the results of [21], where the partial density of the s-type states are 1.5 times larger than that of the p-type states.…”
Section: Electronic Structure Of Basal Surfaces Clusterssupporting
confidence: 75%
See 1 more Smart Citation
“…Comparison of the band shapes calculated in the two considered approaches (Figure 3) allows one to note that, in the cluster approach, the valence band width is larger; however, the forbidden gap is reproduced well. In addition, the analysis of the results of this study makes it possible to associate the band of free states (position b) with the 3s states of aluminum, which correlates with the results of [21], where the partial density of the s-type states are 1.5 times larger than that of the p-type states.…”
Section: Electronic Structure Of Basal Surfaces Clusterssupporting
confidence: 75%
“…The densities of states are obtained by summing all one-electron components of both clusters; they are presented in Figure 3. The figure also shows the densities of states calculated using the results of the DFT calculation for an infinite crystal performed in [21]. In Figure 3, the bands of electronic states calculated in this work are shifted by 9.0 eV so that the maxima of the valence band density calculated by the two methods had the same position in the energy scale (position a).…”
Section: Electronic Structure Of Basal Surfaces Clustersmentioning
confidence: 87%
“…With the increase of MA content, all three degradation temperatures decreased, and these decrements demonstrated that the thermal stability of the MA-modified composites was declined ( Figure 3a); of special note is that the decrease of T 90% was more obvious than others. This might be explained by the promotion of the degradation of composites when a carboxyl group was introduced with the modified poplar fiber in the composites [29]. However, KH550 increased the degradation temperatures of the composites with increases in its content (Figure 3c), which mainly resulted from the reaction between KH550 and the poplar fibers, and a layer of KH550 on the fiber surface could have further improved the thermal stability of the composites [30].…”
Section: Thermal Properties Of Compositesmentioning
confidence: 99%
“…This value was selected as a compromise between accuracy and calculation time. The electron-ion interaction was calculated using the Vanderbilt ultrasoft pseudopotential [37], which has a wide range of applications [38,39] and provides a high speed and accuracy of calculation [40], with the valence electron configurations Fe 3d 6 4s 2 , O 2s 2 2p 4 , N 2s 2 2p 3 , C 2s 2 2p 2 , and H 1s 1 . Structure optimization was performed through the Broyden-Fletcher-Goldfarb-Shanno (BFGS) algorithm [41].…”
Section: Monte Carlo Simulationmentioning
confidence: 99%